Handbook of foot and ankle orthopedics - Shah, Rajiv (Thieme, 2016)
"Foot and ankle orthopedics is the fastest developing orthopedic subspecialty in the Asia-Pacific region and the Handbook of Foot and Ankle Orthopedics is designed to be an indispensable guide for all general as well as specialist orthopedicians. The handbook covers a wide range of topics, including the general rules of foot and ankle examination, their investigation, rationale of prescription of foot and ankle orthotics, various malunions, management of foot and ankle trauma, diagnosis, and the management of common foot and ankle infections. It also explains the art of arthrodesis in a concise yet comprehensive manner. Its content is organized in a pointwise format, supported by algorithms, tables, illustrations and real clinical pictures for easy and quick reference by orthopedic surgeons. The chapters are contributed by internationally-renowned authors with years of clinical experience"--Publisher's description